Gender Differences in Physical, Chemical and Metabolic Factors Involved in Nephrolithiasis - Moyano, Mario Franco (2017)
Kidney stones forming require investigations to detect predisposing metabolic abnormalities. A variety of dietary and metabolic factors may contribute or cause stone formation in nephrolithiasis. Some metabolic causes are hypercalciuria, hypocitraturia, gout, hyperoxaluria, and hyperuricosuria. The aim was to investigate physical, chemical and metabolic abnormalities involved in the risk of lithogenesis in both sex. Observational and cross-sectional retrospective study was undertaken. Total metabolic variables were assessed in the data base, including serum and urine chemistries. 421 patients (20-70 years), 57.5% women (W) and 42.5% men (M), Age (years): 44.6 ± 13.8(W) 43.9 ± 13.9 (M), weight (Kg): 64.4 ± 13.1(W) 85.5 ± 14.5 (M), p< 0.0001. BMI: 24.9 ± 4.7(W) 28.2 ± 4.3 (M), p< 0.0001. Serum uric acid, creatinine, urea (mg/dl) increased significantly in M (p<0.0001) and potassium (mEq/l) p<0.01. Urinary excretion 24 h (mg/dl): phosphorus, uric acid, creatinine, magnesium, sodium (mEq/l), potassium (mM/l) increased significantly in M (p< 0.0001). Creatinine clearance: 111.0 ± 28.4 M and 88.1 ± 24.0 W, p<0.001. Calcium/creatinine: 0.20 ± 0.09 W and 0.13 ± 0.06 M, p< 0.001. Citrate/creatinine: 0.51 ± 0.37 W and 0.28 ± 0.16 M, p< 0.001. Uric acid/creatinine: 0.43 ± 0.15 W and 0.39 ± 0.11 M, p< 0.05. Significantly differences in PTH compared W to M, p< 0.001. No significant differences were found in other parameters studied. The risk of renal stone, forming and some metabolic gender differences were found. The results of these investigations can also be used to help guide therapy to prevent future stone formation.